Myeloid CCN3 protects against aortic valve calcification - Peinan Tu; Qian Xu; Xianming Zhou; Nicolas Villa-Roel; Sandeep Kumar; Nianguo Dong; Hanjoong Jo; Caiwen Ou; Zhiyong Lin (Cell Communication and Signaling, 2023)
Abstract Background Cellular communication network factor 3 (CCN3) has been implicated in the regulation of osteoblast differentiation. However, it is not known if CCN3 can regulate valvular calcification. While macrophages have been shown to regulate valvular calcification, the molecular and cellular mechanisms of this process remain poorly understood. In the present study, we investigated the role of macrophage-derived CCN3 in the progression of calcific aortic valve disease. Methods Myeloid-specific knockout of CCN3 (Mye-CCN3-KO) and control mice were subjected to a single tail intravenous injection of AAV encoding mutant mPCSK9 (rAAV8/D377Y-mPCSK9) to induce hyperlipidemia. AAV-injected mice were then fed a high fat diet for 40 weeks. At the conclusion of high fat diet feeding, tissues were harvested and subjected to histologic and pathologic analyses. In vitro, bone marrow-derived macrophages (BMDM) were obtained from Mye-CCN3-KO and control mice and the expression of bone morphogenic protein signaling related gene were verified via quantitative real-time PCR and Western blotting. The BMDM conditioned medium was cocultured with human valvular intersititial cells which was artificially induced calcification to test the effect of the conditioned medium via Western blotting and Alizarin red staining. Results Echocardiography revealed that both male and female Mye-CCN3-KO mice displayed compromised aortic valvular function accompanied by exacerbated valve thickness and cardiac dysfunction. Histologically, Alizarin-Red staining revealed a marked increase in aortic valve calcification in Mye-CCN3-KO mice when compared to the controls. In vitro, CCN3 deficiency augmented BMP2 production and secretion from bone marrow-derived macrophages. In addition, human valvular interstitial cells cultured with conditioned media from CCN3-deficient BMDMs resulted in exaggerated pro-calcifying gene expression and the consequent calcification. Conclusion Our data uncovered a novel role of myeloid CCN3 in the regulation of aortic valve calcification. Modulation of BMP2 production and secretion in macrophages might serve as a key mechanism for macrophage-derived CCN3’s anti-calcification function in the development of CAVD. Video Abstract